Scientific, Methodological and Organizational Approaches to Conducting Pre-clinical and Expert studies of Substances with Psychoactive Properties - T. L. Malkova; P. S. Mashchenko; A. I. Andreev; D. Yu. Apushkin; E. V. Vikhareva (Разработка и регистрация лекарственных средств)
Introduction. Studying the psychoactive properties of substances is an important task for regulating their circulation. It is relevant both for new psychoactive substances (NPS) that are in illegal circulation and for drugs entering the pharmaceutical market. In this regard, the issue of creating specialized analytical centers for conducting complex chemical and pharmacological studies does not lose its relevance.Aim. The purpose of the work is to develop scientific, methodological and organizational approaches to conducting comprehensive studies of psychoactive substances based on generalizing the work experience of employees of the Regional Test Center (RTC) "Pharmatest" of the Perm State Pharmaceutical Academy, both in the study of new psychoactive substances, withdrawn from illegal circulation, as part of expert studies on behalf of law enforcement agencies, and as part of preclinical studies of new medicines.Materials and methods. When performing the work, experimental and statistical data for 2010–2023 were used. on the study of NPS on the basis of the RTC "Pharmatest" in order to determine the possibility of classifying them as analogues of drugs of abuse, materials on the study of new drugs for the possible presence of psychoactive properties and affinity for certain receptors, approaches to conducting individual stages of expert examinations were assessed and described research, chemical and biological methods used.Results and discussion. The stages of research into new psychoactive substances and the methodology for conducting tests on each of them, as well as the necessary equipment and approaches to interpreting the results obtained, have been determined and scientifically substantiated. The need to create analytical centers to conduct comprehensive expert studies of narcotic substances and preclinical studies of drugs is shown.Conclusion. The developed methodological principles and organizational measures for conducting a comprehensive study of new psychoactive substances are important both for suppressing illegal drug trafficking in order to implement the State anti-drug policy, and for the development of domestic pharmaceuticals, designed to ensure the use of effective and safe medicines in medical practice.